CORDIERITE II: THE ROLE OF CO2 AND H2O - Kolesov B.A.; Geiger C.A. (My University, 2000)
Polarized single-crystal Raman spectra at room temperature and 5 K and polarized infrared spectra at room temperature were obtained from four natural cordierites of different compositions in the wave number region of the CO2 symmetric stretching vibration and the H2O stretching vibrations. The CO2 molecules are preferentially aligned parallel to the X axis, consistent with results from X-ray diffraction and optical studies. The CO2 contents of six natural cordierites, previously studied by powder IR methods (Vry et al. 1990), were determined via Raman spectroscopy. A linear relationship was found between CO2 content and the Raman intensity ratio of the normalized CO2 stretching mode against a Si-O stretching mode. This permits a determination of the CO2 contents in cordierite using micro-Raman measurements. The internal stretching modes between 3500 and 3800 cm−1 were assigned to various types of H2O molecules occurring in the channel cavity. Three different orientations of H2O molecules that have no interactions with alkali cations located at 0,0,0 in the six-membered tetrahedral rings are classified in a static model as Class I H2O molecules. The H···H vector for two of them is parallel to [001], and their molecular planes lie in the XZ and YZ crystal planes. The third type has its H···H vector directed along the X axis and its molecular plane lies in the XZ plane. Two other types of H2O have interactions with the alkali cations located at 0,0,0. They are classified as Class II H2O. They distinguish themselves by the number of H2O molecules bonded to the alkali atoms. The formation of weak hydrogen bonds at low temperatures may explain the appearance of some Raman stretching modes below 200 K. The H2O molecules of Class I-Type I/II are probably dynamically disordered about [001] hopping between orientations in the XY and XZ planes down to 5 K. Class II H2O may also be disordered, but more measurements are required to describe its dynamic behavior.